Hukum mediasi dalam perspektif islam kontemporer - husen, mohamad nur; wafie, slamet (Fakta: Forum Aktual Ahwal Al-Syakhsiyah, 2025)
Mediation is an effective alternative to dispute resolution with a win-win solution approach. However, Supreme Court Regulation (Perma) No. 1 of 2008 limits the scope of mediation to civil disputes only. In this context, Islamic law offers a more comprehensive concept of Sulh, which covers both criminal and civil cases. The concept of Islah in Islamic law emphasizes peace, justice and peaceful resolution of disputes. Therefore, it is necessary to conduct an analysis to expand the scope of mediation based on the principles of Islamic law. This can enrich Indonesia's legal repertoire and increase the effectiveness of dispute resolution, as well as strengthen the role of the state as a mediator. Mediation is one of the alternative ways to resolve disputes. Islamic law is an inseparable part of the legal building in Indonesia, so it is possible that the treasures in Islamic law become input for Indonesian law, including mediation. In Islam, mediation known as Sulh covers a wider scope than the scope of mediation in Perma No. 1 of 2008. This paper will describe the opportunities to expand the scope of mediation in Perma No. 1 of 2008 based on the perspective of Islamic Law, one of which is mediation in criminal cases. The State is not only present as a punisher, but more broadly the State is present as a mediator in criminal cases (public). Mediation in the context of contemporary Islamic law is an alternative dispute resolution method that prioritizes the principles of peace and justice. In the Indonesian judicial system, especially in the Religious Courts, mediation is regulated by Supreme Court Regulation (PERMA) No. 1 of 2008, which requires every civil case to be resolved through mediation before proceeding to the litigation process. The concept of alternative dispute resolution in Islamic law is carried out with the Islah approach with various forms, such as wilayat al-mazalim, al hisbah, and takhim. The State is not only present as a punisher, but more broadly the State is present as a mediator in criminal cases (public).